2020
DOI: 10.1002/ejhf.2016
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cardiopulmonary exercise testing in cardiac amyloidosis

Abstract: In amyloid patients, cardiac involvement dramatically worsens functional capacity and prognosis. We sought to study how the cardiopulmonary exercise test (CPET) could help in functional assessment and risk stratification of patients with cardiac amyloidosis (CA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 27 publications
4
38
0
Order By: Relevance
“…In a recent study on 150 patients with either AL or ATTR CA, peak oxygen consumption (VO 2 ) at cardiopulmonary exercise test was an independent predictor of adverse cardiovascular outcome (all‐cause death or HF hospitalization) as well as peak circulatory power (peak VO 2 × peak systolic blood pressure) and NT‐proBNP. Interestingly, the combination of peak VO 2 <13 mL/kg/min and NT‐proBNP ≥1800 ng/L identified a subgroup of patients at very high risk 112 . Moreover, in this study peak VO 2 alone improved risk stratification over Mayo2012 [net reclassification index (NRI) 0.16] and NAC ATTR staging system (NRI 0.05) in the AL and ATTR CA subgroups, respectively 112 .…”
Section: Biomarkers Of Cardiac Involvementmentioning
confidence: 63%
See 1 more Smart Citation
“…In a recent study on 150 patients with either AL or ATTR CA, peak oxygen consumption (VO 2 ) at cardiopulmonary exercise test was an independent predictor of adverse cardiovascular outcome (all‐cause death or HF hospitalization) as well as peak circulatory power (peak VO 2 × peak systolic blood pressure) and NT‐proBNP. Interestingly, the combination of peak VO 2 <13 mL/kg/min and NT‐proBNP ≥1800 ng/L identified a subgroup of patients at very high risk 112 . Moreover, in this study peak VO 2 alone improved risk stratification over Mayo2012 [net reclassification index (NRI) 0.16] and NAC ATTR staging system (NRI 0.05) in the AL and ATTR CA subgroups, respectively 112 .…”
Section: Biomarkers Of Cardiac Involvementmentioning
confidence: 63%
“…Interestingly, the combination of peak VO 2 <13 mL/kg/min and NT‐proBNP ≥1800 ng/L identified a subgroup of patients at very high risk 112 . Moreover, in this study peak VO 2 alone improved risk stratification over Mayo2012 [net reclassification index (NRI) 0.16] and NAC ATTR staging system (NRI 0.05) in the AL and ATTR CA subgroups, respectively 112 . Another recent study on 309 patients with ATTR CA demonstrated that the addition of diuretic dose (expressed in categories: 0 mg/kg, >0 to 0.5 mg/kg, >0.5 to 1 mg/kg, and >1 to 2 mg/kg) and New York Heart Association (NYHA) class improved the prognostic performance of currently used biomarker‐based staging systems for ATTR CA, namely the NAC ATTR staging system (AUC change from 0.711 to 0.816) and the one proposed by Grogan et al .…”
Section: Biomarkers Of Cardiac Involvementmentioning
confidence: 99%
“…This finding of significant prognostic value of peak CP was also demonstrated in recent study on cardiac amyloid patients. (8) Our study has several limitations. As with other wtATTR studies, the sample size is small due to rarity of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…reviewed the role of circulating biomarkers as tools to guide diagnosis, prognostic stratification, and therapy in CA. The independent prognostic role of cardiopulmonary exercise testing in patients with light chain or transthyretin CA (TTR‐CA) was shown by Nicol et al 5 . in a multicentre study.…”
Section: Cardiac Amyloidosismentioning
confidence: 91%